2020
DOI: 10.1016/j.scitotenv.2020.139121
|View full text |Cite
|
Sign up to set email alerts
|

Soil-geomorphology relationships determine the distribution of the main subalpine grasslands in the Central Pyrenees (NE-Spain)

Abstract: Soil-geomorphology relationships determine the distribution of the main subalpine grasslands in the Central Pyrenees (NE, Spain)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Armas-Herrera et al (2020) showed that patches of Nardus grassland can coexist within a few meters of patches of grasses and herbs that prefer calcareous soils (usually referred to as chalk grassland), resulting in a repeating vegetation mosaic characteristic of certain high-mountain areas of the Pyrenees. This pattern results from differential soil erosion, which creates soil conditions conducive to either chalk grasslands or Nardus grasslands (Badía-Villas et al 2020). The studies by Armas-Herrera et al (2020) and Badía-Villas et al (2020) revealed contrasting soil thickness, stoniness, acid/base status (pH, Ca) and organic matter-related properties among patches of Nardus and chalk grasslands.…”
Section: Introductionmentioning
confidence: 99%
“…Armas-Herrera et al (2020) showed that patches of Nardus grassland can coexist within a few meters of patches of grasses and herbs that prefer calcareous soils (usually referred to as chalk grassland), resulting in a repeating vegetation mosaic characteristic of certain high-mountain areas of the Pyrenees. This pattern results from differential soil erosion, which creates soil conditions conducive to either chalk grasslands or Nardus grasslands (Badía-Villas et al 2020). The studies by Armas-Herrera et al (2020) and Badía-Villas et al (2020) revealed contrasting soil thickness, stoniness, acid/base status (pH, Ca) and organic matter-related properties among patches of Nardus and chalk grasslands.…”
Section: Introductionmentioning
confidence: 99%